2018
DOI: 10.1002/jcp.26576
|View full text |Cite
|
Sign up to set email alerts
|

Let‐7e inhibits TNF‐α expression by targeting the methyl transferase EZH2 in DENV2‐infected THP‐1 cells

Abstract: Tumor necrosis factor α (TNFα), an important inflammatory cytokine, is associated with dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS), a severe pathological manifestation of dengue virus (DENV) infection. However, the regulatory mechanism of microRNA on TNFα is currently unknown. Our study showed that the TNFα expression increased immediately and then later decreased, while a marked increase for the miRNA let-7e was detected in dengue virus type 2 (DENV2)-infected peripheral blood mononuclear cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…However, the role of Ezh2 as the regulator of inflammatory factors was uncovered by recent studies. In Zhang and colleagues' study, it was revealed that inhibition of EZH2 would reduce TNFα expression by depressing nuclear NF‐κB p65 levels. In other research about breast cancer, EZH2 acted as a co‐activator of RelA and RelB (subunits of NF‐κB protein family) to facilitate the expression of TNFα and IL‐6 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of Ezh2 as the regulator of inflammatory factors was uncovered by recent studies. In Zhang and colleagues' study, it was revealed that inhibition of EZH2 would reduce TNFα expression by depressing nuclear NF‐κB p65 levels. In other research about breast cancer, EZH2 acted as a co‐activator of RelA and RelB (subunits of NF‐κB protein family) to facilitate the expression of TNFα and IL‐6 .…”
Section: Discussionmentioning
confidence: 99%
“…let-7e, which has been reported to directly regulate EZH2 expression is only upregulated in SD patients on day 2 and day 4 from fever onset while the expression is downregulated on day 3. Differential expression of EZH2 as a result of upregulation of let-7e expression was implicated in several viral infections including DENV2 infected peripheral blood mononuclear cells (PBMCs) [40]. Therefore, further studies in DENV infected cultured cells may be needed to evaluate the role of let-7e on the differential expression of EZH2 during SD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports show that miR-125a and let-7e are significantly downregulated in many cancers, and downregulation of these miRNAs leads to enhanced tumor progression, chemoresistance, and metastasis despite strong context dependence of the role of miR-125a and let-7e in cancer (3440). Although miR-125a and let-7e are highly expressed in ECs (8, 41), and have been studied in different cellular contexts such as in immune cells, preosteoblasts, and in a variety of cancers (23, 24, 34, 37, 42, 43), their role in EC biology remains unclear. Therefore, it is important to understand the role or regulation of miR-125a and let-7e in tumors as well as in tumor microenvironments such as ECs.…”
Section: Discussionmentioning
confidence: 99%